PENGARUH KOLABORASI TERHADAP KUALITAS PUBLIKASI PENELITIAN KEANEKARAGAMAN HAYATI INDONESIA BERDASARKAN BASIS DATA SCOPUS (1990-2012) - Rizka Rahmaida; Mia Amelia (BERITA BIOLOGI, 2018)
Collaboration becomes trend in scientific publication for last decade. Many previous studies showed that collaboration had impact on quality of publication in terms of citation impact. This study aimed to investigate the influence of different pattern of collaboration on the citation impact of publications on biodiversity research from Indonesian researcher. A one thousand six hundred and ninty nine (1,699) articles were published by researchers affiliated with institution located in Indonesia from 1990-2012 based on Scopus database. Different pattern of collaboration were investigated in different level. Based on the result, only 4.4% of those publications were single author publications, 11.4% of those were intra-institution publications, and 17.4% of those were domestic collaboration. Using linear regression analysis, the result of the study showed that there was a significant positive correlation between the number of authors and the number of citations in international publication on biodiversity research from Indonesian researcher. In addition, publications with a higher number of institutions have received higher number of citations. Publication with a higher number of foreign collaborating countries also received more citations.